2023
DOI: 10.1037/dev0001484
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of child–parent attachment in early childhood and prosociality.

Abstract: Although numerous individual studies have attempted to link child-parent attachment and prosociality, a systematic picture of that relationship requires a meta-analytic approach that considers different dimensions of prosociality and potential moderators. The current meta-analysis examined 41 studies drawn primarily from North America and Europe and published between 1978 to 2020. Child age ranged from 12 to 53 months at the assessment of child-parent attachment and 12 to 108 months at the assessment of prosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The test–retest reliability of the SSP over 1 month is robust (e.g., Goossens et al, 1986; Waters, 1978), and extensive research exists on the predictive validity of the SSP. Specifically, it has been repeatedly shown that infants in secure attachment relationships have more positive behavioral, cognitive, and interpersonal outcomes compared to their insecure counterparts (e.g., Dagan et al, 2021; Deneault et al, 2021; Deneault, Hammond, & Madigan, 2022; Fearon et al, 2010; Groh, Fearon, et al, 2017; Madigan et al, 2013; Van IJzendoorn et al, 1999).…”
Section: Development Of the Strange Situation Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…The test–retest reliability of the SSP over 1 month is robust (e.g., Goossens et al, 1986; Waters, 1978), and extensive research exists on the predictive validity of the SSP. Specifically, it has been repeatedly shown that infants in secure attachment relationships have more positive behavioral, cognitive, and interpersonal outcomes compared to their insecure counterparts (e.g., Dagan et al, 2021; Deneault et al, 2021; Deneault, Hammond, & Madigan, 2022; Fearon et al, 2010; Groh, Fearon, et al, 2017; Madigan et al, 2013; Van IJzendoorn et al, 1999).…”
Section: Development Of the Strange Situation Paradigmmentioning
confidence: 99%
“…SSP. Specifically, it has been repeatedly shown that infants in secure attachment relationships have more positive behavioral, cognitive, and interpersonal outcomes compared to their insecure counterparts (e.g., Deneault et al, 2021;Deneault, Hammond, & Madigan, 2022;Fearon et al, 2010;Madigan et al, 2013;Van IJzendoorn et al, 1999).…”
Section: Secure Avoidant and Resistant Attachmentmentioning
confidence: 99%
“…Moreover, the prevalence of secure infant-mother (51.2%) and secure infantfather (61.2%) attachment as assessed in the SSP in particular, is statistically similar (Madigan et al, 2023). Likewise, as mentioned, associations between maternal and paternal sensitivity and secure attachment with various child outcomes are also similar (Cooke et al, 2022;Dagan et al, 2021;Deneault et al, 2021;Deneault, Hammond, et al, 2023;Madigan et al, 2019;Rodrigues et al, 2021). Taken together, available evidence suggests that there are more similarities than differences in the ways that sensitive caregiving and attachment security with mothers and fathers benefit children's development.…”
Section: Did the Association Differ Between Maternal And Paternal Sen...mentioning
confidence: 70%
“…Our inability to test moderators for insecure types may be due, at least in part, to small sample sizes of child–father dyads that force the grouping of insecure categories of attachment into one group to derive the secure versus insecure contrast. Yet, more recently, there is interest in not only studying child–father dyads, but also in differentiating the antecedents and sequelae of the different types of insecure attachment (e.g., Dagan et al, 2021; Deneault, Bureau, et al, 2022; Deneault, Hammond, et al, 2023; Madigan et al, 2023). Future data could powerfully inform, and help to tailor, attachment-based interventions seeking not only to bolster secure attachment, but minimize the risks of children developing avoidant, resistant, and disorganized attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Early predictors such as children’s experiences of compliance with parental rules or empathy with others should be considered in this context (e.g., Kochanska, 2002; Reese et al, 2007). Advocates of attachment theory also assume that early attachment experiences to significant others have an important influence on the development of both, early prosocial behavior (Deneault et al, 2023; Gross et al, 2017) and the SC (Paulus et al, 2018). Thus, children’s emergent MSC may relate to their attachment experiences.…”
Section: Discussionmentioning
confidence: 99%